Matematika anak usia dini: Analisis kegiatan berhitung terhadap standar pendidikan matematika NCTM - Lestari, Ririn Hunafa; Aprianti, Ema; Hartini, Hartini (IKIP Siliwangi, 2024)
Many academics and practitioners do research and teaching to develop early childhood numeracy skills by involving various learning elements such as teaching methods and learning media. The National Council of Teachers of Mathematics (NCTM) is the largest mathematics teacher organization in the world to explain mathematics education into two standards, namely content standards and process standards. Therefore, this research aims to examine numeracy activities against NCTM mathematics education standards. To discuss this objective, the research method used is a Systematic Literature Review (SLR) of 21 research articles which can be accessed on the Google Scholar website for the year 2022-2023. After the data was obtained, the data was analyzed using thematic data analysis. The research results show that learning elements which include teaching methods and learning media to introduce and develop numeracy skills in early childhood can be used to introduce and develop mathematical abilities in the NCTM mathematics education content standards, namely algebra, geometry, measurement data analysis, and probability.